Dual-Functional Additives Boost Zinc-Ion Battery Electrolyte over Wide Temperature Range - Zhiqiang Dai; Rungroj Chanajaree; Chengwu Yang; Xueqing Zhang; Manunya Okhawilai; Prasit Pattananuwat; Xinyu Zhang; Guanjie He; Jiaqian Qin (Energy Material Advances)
Traditional aqueous electrolyte systems in zinc-ion batteries (ZIBs) often face challenges such as sluggish ion transfer kinetics, dendrite formation, and sudden battery failures in harsh temperature environments. Herein, we introduce a pioneering approach by integrating a bifunctional additive composed of ethylene glycol (EG) and sodium gluconate (Ga) into ZnSO4 (ZSO) electrolyte to overcome these obstacles. The polyhydroxy structures of EG and Ga can reconstruct the hydrogen bond network of H2O to improve its liquid stability, and also adjust the coordination environment around hydrated Zn2+. Additionally, Ga in the H2O–EG mixture leads to the formation of a robust protective layer that promotes uniform deposition of Zn2+ ions and minimizes unwanted side reactions. Therefore, Zn anodes with 40% ZSO–Ga electrolyte can cycle for more than 3,000 h at 25 °C and 800 h at 50 °C. Furthermore, Zn||NH4V4O10 (NVO) full batteries demonstrate remarkable cycle stability, lasting up to 10,000 cycles at 1 A g−1 with a capacity retention of 79.1%. The multifunctional electrolyte additive employed in this study emerges as a promising candidate for enabling highly stable zinc anodes under diverse temperature conditions.